10-year trends in statin utilization in Taiwan: a retrospective study using Taiwan's National Health Insurance Research Database. Issue 5 (17th May 2017) - Hsieh, Hsing-Chun; Hsu, Jason C; Lu, Christine Y
Abstract : Objective: Statins have been commonly used to treat patients with hypercholesterolaemia and to prevent cardiovascular disease (CVD) worldwide. This study examined trends in use of statins in Taiwan from 2002 to 2011. Design: This is a retrospective observational study focusing on the utilisation of statins. Setting: The monthly claims data for statins between 2002 and 2011 were retrieved from Taiwan's National Health Insurance Research Database. Main outcome measures: We calculated the yearly prescription rate per new user for each statin. Products were classified as high-intensity/moderate-intensity/low-intensity statins by type of statin and dosage. Users were also classified based on disease histories. Results: The number of statin users increased from 10 299 (~1.4% of adults) in 2002 to 50 687 (~6.3% of adults) in 2011. Atorvastatin was the most commonly used agent (28.4%–36.7%) during the study period. After 2007, simvastatin ranked second with 21.7% market share, followed by rosuvastatin, a newer agent that exhibited a substantial growth in prescription rates (3.4% in 2005 and 19.5% in 2011). In 2011, 94.0% of new statin users used statin monotherapies, and 6.0% used combination therapies. Use of moderate-intensity statins increased from 49.0% in 2002 to 71.0% in 2011, while high-intensity statins remained low. Patients with history of coronary events or cerebrovascular events were more likely to be prescribed higher intensity statins compared with those without. Prescribing of higher intensity statins was not greater among people with diabetes compared with those without during 2007–2011. Selection of statins did not differ between people with versus without history of myopathy or liver injury. Conclusion: Atorvastatin was the most commonly used statin in Taiwan during 2002–2011. While patients with history of CVD were more likely to be prescribed higher intensity statins compared with those without, this difference was not found comparing those with and without diabetes.